Analysis of Tahfidz Program Entrance Examination Using C4.5 Method for Classification of Learning Groups in The Al-Mawaddah Region of Nurul Jadid Islamic Boarding School, Probolinggo, Indonesia - Wahab Sya'roni; Yulia Sri Devi; Yanuar Ilmansyah (Transactions on Informatics and Data Science, 2024)
The tahfidz program aims to improve understanding and memorization of the Al-Quran in the Al-Mawaddah Region, Probolinggo, Indonesia, including those who organize the Tahfid Qur'an program. This research aims to increase the efficiency and accuracy of analyzing the Tahfid program entrance test results using the C4.5 Algorithm for study group classification and visualizing the results through a web-based interactive application using Streamlit. The C4.5 algorithm is used to build a classification model based on the results of the entrance test criteria. The application of Streamlit as a framework for creating interactive web applications makes it easier for users to enter entrance test data and study group classification results, making it easier to make decisions and plan to learn for Tahfid program administrators. The research results show that the use of the C4.5 Algorithm method and the streamlit application is practical in analyzing the results of the Tahfidz program entrance test and determining study groups, the C4.5 Algorithm succeeded in achieving a high level of accuracy with an accuracy of 94%, then it was implemented using streamlit. With the interactive application, tahfid program managers can carry out the selection and grouping process more quickly and precisely and provide a more targeted learning approach according to the student's ability level.